High triglyceride–glucose index is associated with poor cardiovascular outcomes in Chinese acute coronary syndrome patients without diabetes mellitus who underwent emergency percutaneous coronary intervention with drug-eluting stents - Zhang, Yong; Chu, Chao; Zhong, Zhong; Luo, Yong-bai; Ning, Fei-fei; Guo, Ning (Frontiers in Endocrinology, 2023)
Background: Previous research has supported the association between the triglyceride–glucose index (TyG index) and the incidence and prognosis of cardiovascular disease. However, the association between the TyG index and the prognosis of patients with acute coronary syndrome (ACS) without diabetes mellitus (DM) who underwent emergency percutaneous coronary intervention (PCI) with drug-eluting stents (DESs) has not been thoroughly investigated, and these patients may easily be neglected. Therefore, this study aimed to investigate the association between the TyG index and major adverse cardiovascular and cerebrovascular events (MACCEs) in Chinese ACS patients without DM who underwent emergency PCI with DES. Methods: The total number of ACS patients without DM who underwent emergency PCI with DES for this study was 1650. Ln [fasting triglycerides (mg/dL) ×fasting plasma glucose (mg/dL)/2] is the formula used to calculate the TyG index. According to the TyG index, we classified the patients into two groups. The frequency of the following endpoint events was calculated and compared between the two groups: all-cause death, non-fatal myocardial infarction (MI), non-fatal ischemia stroke, ischemia-driven revascularization and cardiac rehospitalization. Results: After a median of 47 months of follow-up [47 (40, 54)], 437 (26.5%) endpoint events were recorded in total. The TyG index was further demonstrated to be independent of MACCE by multivariable Cox regression analysis (hazard ratio [HR], 1.493; 95% confidence interval [CI], 1.230–1.812; p<0.001). The TyG index≥7.08 group had a considerably greater incidence of MACCE (30.3% vs. 22.7% in the TyG index<7.08 group, p<0.001), cardiac death (4.0% vs. 2.3% in the TyG index<7.08 group, p=0.047), and ischemia-driven revascularization (5.7% vs. 3.6% in the TyG index<7.08 group, p=0.046) than the TyG index<7.08 group. Between the two groups, there was no discernible difference in all-cause death (5.6% vs. 3.8% in the TyG index<7.08 group, p=0.080), non-fatal MI (1.0% vs. 0.2% in the TyG index<7.08 group, p=0.057), non-fatal ischemic stroke (1.6% vs. 1.0% in the TyG index<7.08 group, p=0.272), and cardiac rehospitalization (16.5% vs. 14.1% in the TyG index<7.08 group, p=0.171). Conclusion: For ACS patients without DM who received emergency PCI with DES, the TyG index might be an independent predictor of MACCE.